Unsustainable : The Urgent Need to Transform Society and Reverse Climate Change - Joy, Richard (Book collections on Project MUSE., 2021)
This book shows the way to a more sustainable planet in this critique of approaches to the climate crisis. The authors set out the changes that are needed to social, economic and political values and behaviours, and the roles of governments, corporates and communities, if we are to achieve genuine progress.